Interface engineering of ultrathin Cu(In,Ga)Se 2 solar cells on reflective back contacts - Gouillart, Louis; Cattoni, Andrea; Chen, Wei‐Chao; Goffard, Julie; Riekehr, Lars; Keller, Jan; Jubault, Marie; Naghavi, Negar; Edoff, Marika; Collin, Stéphane (Progress in photovoltaics, 2021)
Cu(In,Ga)Se 2 ‐based (CIGS) solar cells with ultrathin (≤500 nm) absorber layers suffer from the low reflectivity of conventional Mo back contacts. Here, we design and investigate ohmic and reflective back contacts (RBC) made of multilayer stacks that are compatible with the direct deposition of CIGS at 500°C and above. Diffusion mechanisms and reactions at each interface and in the CIGS layer are carefully analyzed by energy dispersive X‐ray (EDX)/scanning transmission electron microscopy (STEM). It shows that the highly reflective silver mirror is efficiently encapsulated in ZnO:Al layers. The detrimental reaction between CIGS and the top In 2 O 3 :Sn (ITO) layer used for ohmic contact can be mitigated by adding a 3 nm thick Al 2 O 3 layer and by decreasing the CIGS coevaporation temperature from 550°C to 500°C. It also improves the compositional grading of Ga toward the CIGS back interface, leading to increased open‐ circuit voltage and fill factor. The best ultrathin CIGS solar cell on RBC exhibits an efficiency of 13.5% (+1.0% as compared to our Mo reference) with a short‐circuit current density of 28.9 mA/cm 2 (+2.6 mA/cm 2 ) enabled by double‐pass absorption in the 510 nm thick CIGS absorber. RBC are easy to fabricate and could benefit other photovoltaic devices that require highly reflective and conductive contacts subject to high temperature processes.